Entering the world of lock and key: the impact of an educational visit to a high secure forensic hospital on psychology students' attitudes towards the patients within. Issue 5 (3rd September 2022) - Griffiths, M.; Tapp, J.; Robertson, E.; Moore, E.
ABSTRACT: Secure forensic hospitals aim to reverse adversity and promote personal safety and mental health well-being for those admitted. These hospitals are also well-placed to make the case for the importance of inclusion and reintegration after a period of enforced community exclusion (through detention under the Mental Health Act). Given the operational and procedural security required for the therapeutic regimes in these settings, only essential visitors are typically given access. This makes it challenging to promote awareness and understanding about patients with forensic and mental health histories. In this study, the impact of a one-day visit to a high-security forensic hospital by psychology students (n = 123), which included face-to-face contact with patients, was studied for its potential to reduce negative attitudes about this population. A comparison group of students who did not attend a visit were also recruited (n = 135). The impact of entering and learning about the hospital, and a conversational exchange with current residents was associated with a significant reduction in negative stereotypes and fear and an increase in compassion and motivation to help. The findings support the use of contact-based educational visits to change negative attitudes and responses towards patients with forensic and mental health histories.